PENGARUH KUALITAS LAYANAN DAN LOKASI TERHADAP CITRA HOTEL, KEPUASAN DAN LOYALITAS TAMU DI HOTEL INNA GARUDA YOGYAKARTA - Afridawati, Wina (Prodi Magister Manajemen FE-UST, 2018)
To determine the effect of service quality and location of the image of the hotel, guest satisfaction and loyalty at Inna Garuda Yogyakarta. The data collection method used was survey method using a questionnaire. In this study, researchers took samples of the guests staying at the Hotel Ina Garuda Yogyakarta amounted to 75 guests, using random sampling techniques. The result show that 1) The quality of service does not affect the companys image, 2) Quality of service has no effect on customer satisfaction, 3) Location affects the image of the company, 4) The location has no effect on customer satisfaction, 5) Corporate Image effect on customer satisfaction, 6) Satisfaction effect on customer loyalty, 7) Image Company effect on customer loyalty, 8) Quality of service impact on customer loyalty, and 9) The location has no effect on customer loyalty.   Keywords: Quality of Service, Location, Citra Hotel, Satisfaction And Loyalty